2013
DOI: 10.1530/erc-13-0329
|View full text |Cite
|
Sign up to set email alerts
|

Leptin receptor maintains cancer stem-like properties in triple negative breast cancer cells

Abstract: Despite new therapies, breast cancer continues to be the second leading cause of cancer mortality in women a consequence of recurrence and metastasis. In recent years, a population of cancer cells has been identified, called cancer stem cells (CSCs) with self-renewal capacity, proposed to underlie tumor recurrence and metastasis. We previously showed that the adipose tissue cytokine LEPTIN, increased in obesity, promotes the survival of CSCs in vivo. Here, we tested the hypothesis that the Leptin Receptor (LEP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(102 citation statements)
references
References 52 publications
5
96
0
Order By: Relevance
“…LEPR is a cytokine receptor that is highly expressed in multiple tumors, including breast cancer, and in breast cancer LEPR expression is directly correlated with poor prognosis (37). LEP is predominately secreted by adipose tissue, and functions as an anorexigenic hormone responsible for appetite suppression and maintenance of EH.…”
Section: Discussionmentioning
confidence: 99%
“…LEPR is a cytokine receptor that is highly expressed in multiple tumors, including breast cancer, and in breast cancer LEPR expression is directly correlated with poor prognosis (37). LEP is predominately secreted by adipose tissue, and functions as an anorexigenic hormone responsible for appetite suppression and maintenance of EH.…”
Section: Discussionmentioning
confidence: 99%
“…Serum from obese patients increased a breast cancer stem cell population by 30% compared with 7% for lean control serum [103]. In breast cancer cell lines, silencing the leptin receptor may reduce cancer stem cell-like properties and EMT transition [104], and treatment of breast cancer cells with leptin from tumour stroma induced stem-like properties [105]. In cell line models of breast cancer, leptin appeared to activate the proinflammatory STAT3 pathway, recruiting G9a and causing repression of miR-200c via epigenetic silencing to induce the EMT stem cell phenotype [106].…”
Section: The Role Of Leptin In the Tumour Microenvironmentmentioning
confidence: 95%
“…Also, TISCs demonstrate increased phosphorylation of pluripotency-associated oncogene Stat3 and induction of OCT4 and SOX2 in response to leptin [122]. It is suggested that leptin receptor plays an important role in the expression of Nanog, OCT4 and SOX2 in BCSCs, viability of BCSCs, proliferation and tumor-initiating activity [123]. These findings raise the possibility that obesity and its associated increased level of leptin-network can act as a mechanistic link between obesity, increased maintenance of cancer stem cells, augmented cancer recurrence, increased distant metastasis and overall poor survival.…”
Section: How Does Leptin Influence Breast Cancer Growth and Metastasis?mentioning
confidence: 99%